Sistem Pengambilan Gelas 250 ml Tertumpuk Dengan Silender Pnuematik Secara Otomatis - Tianur; Nur Khamdi (Jurnal Elektro dan Mesin Terapan, 2021)
Small and medium industries are growing rapidly, one of which is the bottled drinking water (AMDK) industry. Therefore, there are so many studies related to the automatic filling of mineral water in both 250 ml and 600 ml glass packaging. However, this research focuses on an automatic water filling system that is controlled by a microcontroller or PLC so that it ignores the container queuing system in the form of glasses or bottles automatically, in the sense of the research the container queuing system is still done manually. The queue of glasses that are arranged in stacks becomes one of the obstacles, because the distance between the first glass and the second glass and so on is very small and can even be said to be close together. This research focuses on the mechanical system to take the glasses one by one which is arranged in a stack between glasses using acrylic material in the shape of a rectangle at a size of 100mm x 180mm. This mechanical system is to separate the bottom glass from the pile of glasses by pushing the bottom glass separator mechanically, using a pneumatic cylinder that moves horizontally. The results of the research are the process of taking 250 ml glasses one by one in a stack of glasses automatically 100% with a minimum stack of 4 glasses.